1986
DOI: 10.1073/pnas.83.8.2511
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic expression of human insulin gene in transgenic mice.

Abstract: We have investigated the possibility of obtaining integration and expression of a native human gene in transgenic mice. An li-kilobase (kb) human chromosomal DNA fragment including the insulin gene (1430 base pairs) was microinjected into fertilized mouse eggs. This fragment was present in the genomic DNA ofseveral developing animals. One transgenic mouse and its progeny were analyzed for expression of the foreign gene. Synthesis and release of human insulin was revealed by detection ofthe human C-peptide in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…These sequences can replicate the tissue-restricted and metabolically regulated expression pattern of the endogenous insulin gene when linked to a reporter construct in transgenic mice (3,6,20,66) and cell lines (14,25,32,56,57,59). C2 (Ϫ317 to Ϫ311 bp) (15,25,54), A3 (Ϫ201 to Ϫ196 bp) (15,49,50), C1 (Ϫ118 to Ϫ107 bp) (59,73), and E1 (Ϫ100 to Ϫ91 bp) (9,25,71) are the cis-acting enhancer elements within the mammalian insulin gene that are essential for activation.…”
mentioning
confidence: 99%
“…These sequences can replicate the tissue-restricted and metabolically regulated expression pattern of the endogenous insulin gene when linked to a reporter construct in transgenic mice (3,6,20,66) and cell lines (14,25,32,56,57,59). C2 (Ϫ317 to Ϫ311 bp) (15,25,54), A3 (Ϫ201 to Ϫ196 bp) (15,49,50), C1 (Ϫ118 to Ϫ107 bp) (59,73), and E1 (Ϫ100 to Ϫ91 bp) (9,25,71) are the cis-acting enhancer elements within the mammalian insulin gene that are essential for activation.…”
mentioning
confidence: 99%
“…These earlier studies showed that expression of the human gene was limited to the pancreatic B cells of such mice (20,(32)(33)(34)(35)(36), although more recently, it has been found that low levels of human insulin mRNA can also be detected in other tissues, including the brain, in one particular line oftransgenic mice (S. J. Chan and D. Steiner, personal communication). Both the synthesis and the release ofhuman insulin were regulated by glucose in much the same manner as the two endogenous mouse insulins.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of the human insulin gene under the control of its own promoter in transgenic mice has been described by other groups (32)(33)(34)(35)(36) as well as our own (20). These earlier studies showed that expression of the human gene was limited to the pancreatic B cells of such mice (20,(32)(33)(34)(35)(36), although more recently, it has been found that low levels of human insulin mRNA can also be detected in other tissues, including the brain, in one particular line oftransgenic mice (S. J. Chan and D. Steiner, personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Rodents have two nonallelic insulin genes (I and II), which differ in their number of introns and chromosomal locations (45). The equivalent region of the human insulin gene has also been shown to direct cell-specific expression within transgenic mice (9,17,39).Experiments conducted with insulin-and non-insulin-producing cell lines have demonstrated that the 5'-flanking sequences of the insulin gene that are essential for pancreatic ,3-cell-type-specific expression reside between bp -340 and -91 relative to the transcription start site (for a review, see reference 44). This region exhibits enhancer-like properties and is regulated by both positively and negatively acting transcription factors (12,13,15,31,55).…”
mentioning
confidence: 99%
“…Rodents have two nonallelic insulin genes (I and II), which differ in their number of introns and chromosomal locations (45). The equivalent region of the human insulin gene has also been shown to direct cell-specific expression within transgenic mice (9,17,39).…”
mentioning
confidence: 99%